2008
DOI: 10.1186/1465-9921-9-24
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the impact of ozone on survival and alveolar macrophage function of mice after Klebsiella pneumoniae infection

Abstract: Background: Sex differences have been described in a number of pulmonary diseases. However, the impact of ozone exposure followed by pneumonia infection on sex-related survival and macrophage function have not been reported. The purpose of this study was to determine whether ozone exposure differentially affects: 1) survival of male and female mice infected with Klebsiella pneumoniae, and 2) the phagocytic ability of macrophages from these mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
166
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(182 citation statements)
references
References 51 publications
15
166
0
1
Order By: Relevance
“…A recent study by Mikerov and coworkers reported that male mice were more susceptible than female mice to lung infection with Klebsiella pneumoniae but that this pattern was reversed in mice that had been exposed to ozone before establishment of the infection (30). Tissue damage associated with carrageenan-induced pleurisy in rats was reported to be attenuated by estrogen; this effect was blocked by coadministration of the ER antagonists ICI 182780 or tamoxifen, suggestive of a receptor-mediated effect (31).…”
Section: Nonallergic Lung Inflammation and Acute Lung Injurymentioning
confidence: 99%
“…A recent study by Mikerov and coworkers reported that male mice were more susceptible than female mice to lung infection with Klebsiella pneumoniae but that this pattern was reversed in mice that had been exposed to ozone before establishment of the infection (30). Tissue damage associated with carrageenan-induced pleurisy in rats was reported to be attenuated by estrogen; this effect was blocked by coadministration of the ER antagonists ICI 182780 or tamoxifen, suggestive of a receptor-mediated effect (31).…”
Section: Nonallergic Lung Inflammation and Acute Lung Injurymentioning
confidence: 99%
“…Akciğer hastalıklarının insidans ve ağırlığını inceleyen hayvan çalışmaları da bu sonucu desteklemektedir. Yeni bir hayvan çalışmasında da kadın seks hormonlarının akciğer hastalıklarına karşı koruyucu etkisi gösterilmiştir 4,5 .…”
Section: şEkil 2 Olgu 5 Toraks Tomografisiunclassified
“…Indeed, in the U.S., influenza and pneumonia are the fifth leading cause of death in patients over the age of 65 (37). Although it remains unclear why the elderly are more susceptible to pneumonia and other lung diseases, it is interesting to note that similar increases in susceptibility may follow exposure to ozone (21,38,59) or high levels of therapeutic oxygen (4), strongly suggesting that oxidative processes may be involved.Reactive oxygen and nitrogen species (RONS) play a very prominent role in lung biology and pathology. They come from a variety of exogenous sources, and endogenous RONS may be generated by mechanisms that macrophages and other immune cells in the lung use to initiate and regulate inflammation and disable invading pathogens.…”
mentioning
confidence: 99%
“…Indeed, in the U.S., influenza and pneumonia are the fifth leading cause of death in patients over the age of 65 (37). Although it remains unclear why the elderly are more susceptible to pneumonia and other lung diseases, it is interesting to note that similar increases in susceptibility may follow exposure to ozone (21,38,59) or high levels of therapeutic oxygen (4), strongly suggesting that oxidative processes may be involved.…”
mentioning
confidence: 99%